The Phenomenological Impact of System Building on Spiritual, Mental, Body and Family Wholeness - Joachim Okoroafor; Chukwu Peter Damian Ezechi (International Journal on Orange Technologies, 2023)
Everything in the universe is built to function via an order and nothing functions in disorder. The universe is an ordered phenomenon; the human body is an ordered unit; the earth is an arranged sphere. All realities are built to function by laws. These laws are systems that make everything in the universe to be stable, predictable and automatic. This work which has the human person as its central focus is out to give a phenomenological weight on the reality of the intricate nature of man via his spirit, mind and body. It also extended its ambient to an area of social strata which is the family wholeness. The spirit of man is his divine reality; the mind is his reasoning faculty, the body is his mechanical tool and the family, his relationship setting. Therefore, for any of this human nature to remain healthy for the unification of others a system must be built in accordance with its nature. Hence, this work is out to open the mind of man to the reality of his nature via system building.